Influence Of Fishery Resources, Good Governance, and Human Resources To Economic Sustainability Through Fishery Performance Using Pathway Analysis - Agustino*, Rinto; Susilastuti, Darwati; Sugiyanto, Sugiyanto (Universitas Syiah Kuala, 2023)
The study aims for knowing the influence of potency source power fisheries, good governance, and resources power human, against performance fishery as well as sustainability economy fishery. Study this using approach quantitative with an analysis path. The sample inside the study is some stakeholders in the form of Representatives of the Ministry of Maritime Affairs and Fisheries (KKP), Representatives of the Maritime Affairs and Fisheries Service, and organization fisherman fish caught in the withdrawal process sample. Remember that population in the study this character infinite or not finite, so the sampling technique used to get the sample is the non-probability sampling method, namely quota sampling. Amount sample study is taken using the technique quota sampling on research this is as many as 200 individuals as field stakeholders fishery. Research results show that source power fishery by direct take effect was however not significant to sustainability economy fisheries and _ no direct take effect significant to sustainability economy fishery. In addition, good governance by direct take effect but not significant to sustainability economy fisheries, and no direct take effect significant to sustainability economy fishery. and source power man by direct take effect negative however no significant to sustainability economy fishery as well as performance fishery take effect however no significant to sustainability economy fishery